2021
DOI: 10.1007/s11356-021-17387-5
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of p-xylene—a comparison of three psychrophilic Pseudomonas strains through the lens of gene expression

Abstract: p-Xylene is considered a recalcitrant compound despite showing a similar aromatic structure to other BTEXs (benzene, toluene, ethylbenzene, xylene isomers). This study evaluated the p-xylene biodegradation potential of three psychrophilic Pseudomonas strains (Pseudomonas putida S2TR-01, Pseudomonas synxantha S2TR-20, and Pseudomonas azotoformans S2TR-09). The p-xylene metabolism-related catabolic genes (xylM, xylA, and xylE) and the corresponding regulatory genes (xylR and xylS) of the selected strains were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Our previous study showed that cold-active XMO and C1,2D complete dearomatization of p-xylene and no intermediate was detected in soil and groundwater samples. The mixture of theses enzymes is suitable for conditions that rapid remediation is needed (such as cold sites) and also stimulate the degradation processes in the contaminated site (Miri et al, 2022b). In this study, free and immobilized enzymes (XMO and C1,2D) were used for p-xylene biodegradation (Figure 5).…”
Section: Biodegradation Of P-xylenementioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study showed that cold-active XMO and C1,2D complete dearomatization of p-xylene and no intermediate was detected in soil and groundwater samples. The mixture of theses enzymes is suitable for conditions that rapid remediation is needed (such as cold sites) and also stimulate the degradation processes in the contaminated site (Miri et al, 2022b). In this study, free and immobilized enzymes (XMO and C1,2D) were used for p-xylene biodegradation (Figure 5).…”
Section: Biodegradation Of P-xylenementioning
confidence: 99%
“…Cold-active enzymes have the potential to provide greater value in terms of sustainable immobilization and production and may be preferred due to their higher catalytic activity compared to their mesophilic counterparts for the biodegradation of contaminants in cold environments. Our previous finding also showed that the inherent instability of these enzymes is one of the important challenges in the industrial and commercial application of these enzymes (Miri et al, 2021a;Miri et al, 2022b). However, the reusability of immobilized enzymes on solid carriers for soil matrices such as biochar was not feasible (Miri et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ding et al [102] achieved 97.1% bioremediation efficiency of naproxen-contaminated water using Cymbella sp. In addition, studies have shown the possibility of microbiological activity for the degradation of organic compounds such as naphthalene [103], xylene [104] and PAHs [105]. Research by Jiang et al [106] found that bacteria exposed to Cr 6+ experience oxidative stress, thereby reducing their bioremediation efficiency.…”
Section: Recent Knowledge On Biological Remediation Of Soil Water And...mentioning
confidence: 99%